Fluctuating Asymmetry and Geometric Morphometrics in A New Species of Whip Spiders (Charontidae, Amblypygi) Collected from Initao National Park, Misamis Oriental, Philippines - Godinez, Jenefer; Torres, Mark Anthony; Demayo, Cesar (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Whip spiders belong to the less well-studied arachnid order Amblypygi. Here, fluctuating asymmetry (FA) and geometric morphometrics analyses are used as tools to assess the between-sex differences of the sampled amblypygids that are believed to belong under a new species of the Genus Charon. Metric evaluation of the structures corresponding to the left and right sides of the whip spiders was conducted through a series of tests for fluctuating asymmetry (FA) study. Results show that of the 72 traits measured, only three characters that correspond to leg 3 femur length, leg 3 patellar length and leg 4 basitibia 3 length are most ideal in FA study because they did not exhibit size dependence, anti asymmetric or directional asymmetry. Geometric morphometrics analyses using centroid size, Procrustes fitting, thin plate spline (TPS) and warps functions, Euclidean Distance Matrix Analysis (EDMA), elliptic Fourier analysis (EFA) and eigenshape analysis (EA) show that the females exhibit greater diversity in the shapes of the carapace, the sternal area and the opisthosoma of the whip spiders. Further thorough investigations on the characteristics of the samples collected from Initao National Park, Misamis Oriental have to be done to confirm whether the specimens merit a new species status.